Characterization of sevoflurane effects on Per2 expression using ex vivo bioluminescence imaging of the suprachiasmatic nucleus in transgenic rats. (June 2016) - Matsuo, Izumi; Iijima, Norio; Takumi, Ken; Higo, Shimpei; Aikawa, Satoko; Anzai, Megumi; Ishii, Hirotaka; Sakamoto, Atsuhiro; Ozawa, Hitoshi
Highlights: We examined the effect of sevoflurane on Per2 expression in the SCN. The bioluminescence of Per2-dluc transgene was used as a marker of Per2 expression. There was no intra-SCN spatial difference in susceptibility to sevoflurane. Sevoflurane affected bioluminescence rhythm in time-dependent manner. Sevoflurane may inhibit Per2 expression via GABAergic signal transduction. Abstract: The inhalation anesthetic sevoflurane suppresses Per2 expression in the suprachiasmatic nucleus (SCN) in rodents. Here, we investigated the intra-SCN regional specificity, time-dependency, and pharmacological basis of sevoflurane-effects. Bioluminescence image was taken from the SCN explants of mPer2 promoter-destabilized luciferase transgenic rats, and each small regions of interest (ROI) of the image was analyzed. Sevoflurane suppressed bioluminescence in all ROIs, suggesting that all regions in the SCN are sensitive to sevoflurane. Clear time-dependency in sevoflurane effects were also observed; application during the trough phase of the bioluminescence cycle suppressed the subsequent increase in bioluminescence and resulted in a phase delay of the cycle; sevoflurane applied during the middle of the ascending phase induced a phase advance; sevoflurane on the descending phase showed no effect. These results indicate that the sevoflurane effect may depend on the intrinsic state of circadian machinery. Finally, we examined the involvement of GABAergic signal transduction in the sevoflurane effect. Co-application of both GABAA and GABAB receptor antagonists completely blocked the effect of sevoflurane on the bioluminescence rhythm, suggesting that sevoflurane inhibits Per2 expression via GABAergic signal transduction. Current study elucidated the anesthetic effects on the molecular mechanisms of circadian rhythm.